2011
DOI: 10.1590/1808-1657v78p0232011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Do Silício Na Intensidade Da Cercosporiose E Na Nutrição Mineral De Mudas De Cafeeiro

Abstract: RESUMO O presente trabalho objetivou estudar o efeito do silício na intensidade da cercosporiose e na nutrição mineral de mudas de cafeeiro. No experimento 1, testou-se seis doses de ácido silícico (0, 0,5; 1; 2; 4 e 6 g kg–1 de solo) em mudas da cultivar Catuaí Vermelho IAC 99 inoculadas com o fungo Cercospora coffeicola. No experimento 2, foram realizadas microanálises de raios-X para a avaliação de nutrientes presentes nas folhas das mudas de cafeeiro das cultivares Topázio MG1190 e Icatu Precoce IAC 3282, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In this study, no significant differences were observed among the inoculated and non-inoculated genotypes of coffee plants with C. coffeicola regarding total soluble phenolic compounds and soluble lignin levels. Similar results have been reported elsewhere on this pathosystem [25,26]. Since phenolic compounds and lignin are produced as a physical and chemical defense mechanism against pathogen attacks [27,28,29], it was expected that the inoculated genotypes would present higher levels of these metabolites as compared to non-inoculated ones.…”
Section: Vastatrixsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, no significant differences were observed among the inoculated and non-inoculated genotypes of coffee plants with C. coffeicola regarding total soluble phenolic compounds and soluble lignin levels. Similar results have been reported elsewhere on this pathosystem [25,26]. Since phenolic compounds and lignin are produced as a physical and chemical defense mechanism against pathogen attacks [27,28,29], it was expected that the inoculated genotypes would present higher levels of these metabolites as compared to non-inoculated ones.…”
Section: Vastatrixsupporting
confidence: 86%
“…elsewhere on this pathosystem [25,26]. Since phenolic compounds and lignin are produced as a physical and chemical defense mechanism against pathogen attacks [27,28,29], it was expected that the inoculated genotypes would present higher levels of these metabolites as compared to non-inoculated ones.…”
Section: Vastatrixmentioning
confidence: 99%
“…Furthermore, cultivars with less robust symbiosis traits often require higher levels of fertilisation. For example the coffee cultivar Caturra supports mycorrhizal fungi with reduced hyphal length compared to other cultivars and has an unusually high requirement for fertilisation (Abruña et al, 1969;Botelho et al, 2011;Lebrón et al, 2012).…”
Section: Introductionmentioning
confidence: 99%